Keberlanjutan Virtual Criminal Court dalam Perspektif Ius Constituendum - Fira Mubayyinah Mubayyinah (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2021)
Abstract This research is based on the development of virtual trials during the pandemic. This paper examines and reflects and sees the urgency of the sustainability of criminal court e-court in the future. In the judiciary, the use of technology has not been maximally used for the benefit of law enforcement in serving the community. During the Covid-19 epidemic, almost all activities depended on the existence of technology, including law enforcement and services for people seeking justice. The phenomenon of virtual trial implementation during the Covid-19 pandemic provides many lessons and new awareness regarding the importance of reform in criminal justice systems. Various obstacles, both in juridical and empirical aspects, are modalities for correcting criminal justice systems in the future. This research is a normative juridical study using a statutory approach, with primary, secondary and tertiary legal materials then analyzed by descriptive analysis. The results of the study conclude that the implementation of virtual civil court during the pandemic is a form of modernization in criminal justice systems that must be continued in the future. There are at least three reasons for the sustainability of the virtual civil court, namely political, sociological and practical. These three considerations serve as the justification for the formulation of policies on the use of technology in the judiciary. Keywords : Virtual Civil Court, Ius Constituendum